The role of prostatitis in prostate cancer: meta-analysis. - Junyi Jiang; Jinyi Li; Zhang Yunxia; Hong Zhu; Junjiang Liu; Chris Pumill (PLoS ONE)
Objective Use systematic review methods to quantify the association between prostatitis and prostate cancer, under both fixed and random effects model. Evidence acquisition Case control studies of prostate cancer with information on prostatitis history. All studies published between 1990-2012, were collected to calculate a pooled odds ratio. Selection criteria the selection criteria are as follows: human case control studies; published from May 1990 to July 2012; containing number of prostatitis, and prostate cancer cases. Evidence synthesis In total, 20 case control studies were included. A significant association between prostatitis and prostate cancer was found, under both fixed effect model (pooled OR=1.50, 95%CI: 1.39-1.62), and random effects model (OR=1.64, 95%CI: 1.36-1.98). Personal interview based case control studies showed a high level of association (fixed effect model: pooled OR=1.59, 95%CI: 1.47-1.73, random effects model: pooled OR= 1.87, 95%CI: 1.52-2.29), compared with clinical based studies (fixed effect model: pooled OR=1.05, 95%CI: 0.86-1.28, random effects model: pooled OR= 0.98, 95%CI: 0.67-1.45). Additionally, pooled ORs, were calculated for each decade. In a fixed effect model: 1990's: OR=1.58, 95% CI: 1.35-1.84; 2000's: OR=1.59, 95% CI: 1.40-1.79; 2010's: OR=1.37, 95% CI: 1.22-1.56. In a random effects model: 1990's: OR=1.98, 95% CI: 1.08-3.62; 2000's: OR=1.64, 95% CI: 1.23-2.19; 2010's: OR=1.34, 95% CI: 1.03-1.73. Finally a meta-analysis stratified by each country was conducted. In fixed effect models, U.S: pooled OR =1.45, 95%CI: 1.34-1.57; China: pooled OR =4.67, 95%CI: 3.08-7.07; Cuba: pooled OR =1.43, 95%CI: 1.00-2.04; Italy: pooled OR =0.61, 95%CI: 0.13-2.90. In random effects model, U.S: pooled OR=1.50, 95%CI: 1.25-1.80; China: pooled OR =4.67, 95%CI: 3.08-7.07; Cuba: pooled OR =1.43, 95%CI: 1.00-2.04; Italy: pooled OR =0.61, 95%CI: 0.13-2.90. Conclusions the present meta-analysis provides the statistical evidence that the association between prostatitis and prostate cancer is significant.